2012
DOI: 10.1016/j.jeconom.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling college major choices using elicited measures of expectations and counterfactuals

Abstract: We examine differences in minority science graduation rates among University of California campuses when racial preferences were in place. Less-prepared minorities at higherranked campuses had lower persistence rates in science and took longer to graduate. We estimate a model of students college major choice where net returns of a science major differ across campuses and student preparation. We find less-prepared minority students at top-ranked campuses would have higher science graduation rates had they atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
276
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 358 publications
(288 citation statements)
references
References 35 publications
11
276
0
1
Order By: Relevance
“…There would be negative value in alluring students into a major which might not suit them and which they might later regret. (Arcidiacono, Hotz, & Kang, 2012) Aptitude in major Difficulty of major Subject self-efficacy (Alexander & Twinomurinzi, 2012) TRA experiential belief SCCT self-efficacy…”
Section: Discussion Of Resultant Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…There would be negative value in alluring students into a major which might not suit them and which they might later regret. (Arcidiacono, Hotz, & Kang, 2012) Aptitude in major Difficulty of major Subject self-efficacy (Alexander & Twinomurinzi, 2012) TRA experiential belief SCCT self-efficacy…”
Section: Discussion Of Resultant Modelmentioning
confidence: 99%
“…The literature on economic modelling for college career choice has shown that future expected earnings, preference for work and ability to do coursework are dominant career choice factors (Arcidiacono, Hotz, & Kang, 2012) as well as enjoying coursework, finding fulfillment in potential jobs, and gaining the approval of parents (Zafar, 2013). Differences between genders have been found with female students considering nonpecuniary outcomes at university as most important while pecuniary or financial outcomes realisedat the workplace are important for males (Zafar, 2013).…”
Section: Is Career Choice Literaturementioning
confidence: 99%
See 3 more Smart Citations